2020
DOI: 10.1186/s12864-020-6737-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of number of annual rings and tree ages on genomic predictive ability for solid wood properties of Norway spruce

Abstract: Background: Genomic selection (GS) or genomic prediction is considered as a promising approach to accelerate tree breeding and increase genetic gain by shortening breeding cycle, but the efforts to develop routines for operational breeding are so far limited. We investigated the predictive ability (PA) of GS based on 484 progeny trees from 62 half-sib families in Norway spruce (Picea abies (L.) Karst.) for wood density, modulus of elasticity (MOE) and microfibril angle (MFA) measured with SilviScan, as well as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…Implementation of GS in tree breeding is underway with recent publications in eucalypts [61,[74][75][76][77], white spruce [78][79][80], black spruce (Picea mariana [Mill.] BSP) [60], interior spruce [39,70], Norway spruce [68,81,82], loblolly pine [58,83,84], lodgepole pine (Pinus contorta Douglas) [85] and maritime pine [66,67]. GS was adopted in tree breeding in the last decade and different methods to estimate prediction efficiencies or accuracies of the cross-validated genomic predictions models have been implemented [2,86].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of GS in tree breeding is underway with recent publications in eucalypts [61,[74][75][76][77], white spruce [78][79][80], black spruce (Picea mariana [Mill.] BSP) [60], interior spruce [39,70], Norway spruce [68,81,82], loblolly pine [58,83,84], lodgepole pine (Pinus contorta Douglas) [85] and maritime pine [66,67]. GS was adopted in tree breeding in the last decade and different methods to estimate prediction efficiencies or accuracies of the cross-validated genomic predictions models have been implemented [2,86].…”
Section: Discussionmentioning
confidence: 99%
“…The locations of the annual rings were identified, as well as of their compartments of earlywood (EW), transitionwood (TW) and latewood (LW), using the “20–80 density” definition 45 , established for use in different types of studies 46 48 . Averages for all rings and their compartments were calculated for the traits and organised to be ready for use in continued genetic evaluations, such as the work on solid wood traits 10 , on tracheid traits 49 and for wood traits 22 , genomic selection 50 and influences of age and weather 51 . The traits addressed in the current work are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Sequence capture genotyping may be a useful alternative to DNA chips in GS of forest trees. It was used for genotyping Picea abies [54][55][56] and Pinus radiata [67], and was the only method applied in all GS studies on Douglas-fir [19,63,72]. A comparison of two genotyping methods-sequence capture followed by next generation sequencing (NGS) versus EucHIP60K.br-showed their equivalence in terms of genomic prediction of the traits of interest in eucalyptus [44].…”
Section: Complex Genome Genotypingmentioning
confidence: 99%
“…Unlike phenotypic mass selection based on an ancestral relationship matrix (matrix A), genomic prediction relies on a marker-based relationship matrix (matrix G), which provides a more accurate assessment of genetic similarity [56]. Generally, the studies showed the superiority of marker-based models over pedigree-based models.…”
Section: Parametric and Nonparametric Modelsmentioning
confidence: 99%
See 1 more Smart Citation